Between‐country harmonization and differences of the Lifetime of Experiences Questionnaire (LEQ) for lifespan complex mental activity assessment: Neuropsychology/Neuropsychological profiles of dementia: Valid biomarkers?. (7th December 2020) - Ourry, Valentin; Marchant, Natalie L; Schild, Ann‐Katrin; Wirth, Miranka; Coll‐Padros, Nina; Reyrolle, Leslie; Bachelet, Romain; Whitfield, Tim; Demnitz‐King, Harriet; Boton, Maëlle; Lebahar, Julie; Gonneaud, Julie; et al.
Abstract: Background: The Lifetime of Experiences questionnaire (LEQ, Valenzuela and Sachdev, 2007) is an instrument that comprehensively assesses mental activity (education/occupation and leisure activities) across the lifespan (13‐30, 30‐65, 65‐present). The LEQ has been associated with brain health outcomes and cognitive decline. Challenges for the use of this questionnaire across countries include the different education systems and occupation classifications. The objectives of this study were to (1) harmonize the LEQ across Spain, United Kingdom (UK), France and Germany, (2) assess its correlation with a similar tool and (3) assess between‐country differences. Method: The LEQ was administered to 359 cognitively unimpaired older adults (age: 71.2 ± 6 years, education: 13.2 ± 3.5 years) from IMAP+ and Medit‐Ageing European projects. The original scale was translated from English to Spanish, French and German by a professional translation service and iteratively edited by native speakers. Education systems and classification of occupations were harmonized considering between‐country differences and in line with international guidelines. Scoring guidelines were adapted to allow between‐country comparison. We performed Pearson correlations with a similar instrument, the Cognitive Activities Questionnaire (CAQ, Wilson et al., 2003). Between‐country differences were assessed using ANOVA models. Result: There were no between‐country differences in participant's age and education (p>0.1). Between and within countries, the total LEQ score showed moderate to strong associations with the total CAQ score (full sample: r=0.48, Spain: r=0.74, UK: r=0.56, France: r=0.46, all p<0.001; Germany: r=0.41, p<0.05) (Figure 1). Correlation coefficients between the CAQ and LEQ were stronger within (all r>0.35) than between (all r≤0.35) periods. We observed between‐countries differences in lifespan mental activities (p=0.019, Spain > France and Germany > France), notably, during young adulthood (p=0.01, Germany > France) and late life (p=0.01, Spain > UK, Spain > France) (Figure 2). These differences were explained by leisure activities engagement rather than by differences in education and occupation (p<0.001, Young adulthood and Midlife: Spain > UK & France, Germany > France; Late life: Spain > UK & France & Germany) (Figure 3). Conclusion: The harmonized LEQ allowed comparison of complex mental activities ‐ including education and occupation ‐ across countries and was related to another questionnaire measuring mental activity across the lifespan.